Introduction of cow manure biogas using the HDPE geomembrane model in Pinogu, Gorontalo - Bambang Susilo; Hendrix Yulis Setyawan; Muhammad Arwani; Kiki Fibrianto; Yudin Yudiawan Maksum; Azwar Lahusin; Irwan Bempah; Wafa Nida Faida Azra; Riska Ayu Lestari; Rizki Putra Samudra; Arya Nugraha Hananto; Muhammad Bagaskara Wiratirta; Essa Noer Bhakty Mulia; Amelia Amelia; Fahmi Akbar Yuliansyah; I Kadek Olin Adi Wiguna; Djatmiko Bagus Wibowo (Universitas Muhammadiyah Magelang, 2023)
Pinogu sub-district is an organic area in Bone Bolango district, Gorontalo province with abundant cattle potential. Behind a large number of cows in the Pinogu area, a new problem arises in the form of cow manure scattered on the streets. One of the technologies developed to overcome this problem is the introduction of biogas as a solution for utilizing cow manure which is environmentally friendly renewable energy. The digester model produced is a tubular HDPE (high-density polyethylene) geomembrane that has the advantages of being cheap, durable, and suitable for construction in the Pinogu area which has shallow groundwater characteristics. The process of constructing the digester was carried out for 10 days at the house of a resident in Pinogu Induk Village with the stages of site survey, design of the biogas installation unit, introduction, and training on constructing the digester to test the flame. Gas can be used after 5 days of filling cow dung into the digester. In addition to biogas, the remaining results of fermentation and degradation of cow dung can be used as liquid or solid organic fertilizer. It is hoped that with the construction of the HDPE geomembrane model biogas, the community will be able to take advantage of the potential of cow dung as an alternative fuel or renewable energy that is environmentally friendly.